The Book of guys : stories - Keillor, Garrison (New York, N.Y., U.S.A. : Viking, 1993)
A collection of stories about men in trouble - where manhood is a problem to be overcome rather than an opportunity for achievement.
Lonesome Shorty -- The Chuck show of television -- The mid life crisis of Dionysus -- Buddy the leper -- Mr. St. Paul -- That old picayune moon -- Marooned -- Don Giovanni -- Roy Bradley, boy broadcaster -- Gary Keillor -- Omoo the wolf boy -- The country mouse and the city mouse -- Casey at the bat (Road game) -- Herb Johnson, the god of Canton -- Earl Grey -- Winthrop Thorpe Tortuga -- Al Denny -- George Bush -- Christmas in Vermont -- Norman conquest -- Zeus the Lutheran
Keywords: Men -- United States -- Fiction; Humorous fiction